(untitled) (Research, Society and Development, 2022)
This article proposes to reflect on human action as a uniqueness that promotes sustainable development in the perspective of participatory and shared progress. In this sense, the question that guides the reflection is: why ethics and economics have distanced themselves in such a way that there is an economy without ethics and an ethics without economics? The research aims to describe human action as the necessary praxis for sustainability. As for the methodology, the research is exploratory and analytical, with a qualitative approach and was carried out through a literature review using the deductive method. It is concluded that it is necessary that the praxis be guided in the perspective of an ethical economy, which gives sustainability to human dignity, for this to occur, it is necessary to overcome the dichotomy and the Manichaeism that relativizes the unit of sustainable, participatory, shared and integral development. Income distribution helps to mitigate hunger and abandonment scenarios, however, it is necessary to adopt subsidiarity and solidarity processes, oriented to the formation of the common good, in order to mitigate vulnerability scenarios.